Manumycin and gliotoxin derivative KT7595 block Ras farnesylation and cell growth but do not disturb lamin farnesylation and localization in human tumour cells. - Nagase, T. (Nature Publishing Group, 1997)
Recently, many inhibitors of farnesyl protein transferase (FPTase) have been identified. Some of them interrupt cell growth in addition to Ras and nuclear lamin processing of Ras-transformed cells. We have tested the effect of the FPTase inhibitors manumycin, an analogue of farnesyl diphosphate, and KT7595, a gliotoxin derivative, on Ras farnesylation, DNA synthesis and the anchorage-dependent and -independent growth of human colon carcinoma (LoVo), hepatoma (Mahlavu and PLC/PRF/5) and gastric carcinoma (KATO III). Both drugs severely inhibited DNA synthesis, cellular proliferation and Ras farnesylation in LoVo and moderately reduced them in Mahlavu and PLC/PRF/5 but not in KATO III. Complete sequencing of ras genes, however, revealed that LoVo and KATO III have activated Ki-ras and activated N-ras, respectively, whereas Mahlavu and PLC/PRF/5 have no activated ras. We next checked whether the inhibition of the cellular proliferation is due to the blocking of nuclear lamin function. Neither drug disturbed lamin farnesylation and localization, as demonstrated using metabolic labelling, immunoblotting and indirect immunofluorescence. These results indicate that manumycin and KT7595 can inhibit Ras farnesylation and cell growth without disturbing the farnesylation and localization of the lamins on human tumour cell lines. IMAGES: